Socio-economic baseline, economic feasibility study and processing activities ASGM in Obi Island, South Halmahera District, North Maluku Province, Indonesia - Angella Natalia Ghea Puspita; Yanto Sudiyanto; Irwan Haryanto; Quinta Nadya Madra (Brawijaya University, 2023)
Artisanal and Small-Scale Gold Mining (ASGM) is mining of gold deposits with simple physical and chemical characteristics using simple equipment and technology. In 2005, total mercury release in the environment in ASGM was more than twice from this sector, around 35% of total mercury, with an annual estimate at 727 tons, becoming the largest global resource of anthropogenic mercury release. In Indonesia, total mercury released to the environment is estimated at 340 metric tons per year and also among the top 3 global emitters of mercury, with 57.5% from the ASGM sector, where 60% is being emitted to air, 20% to water, and the remaining 20% to land. The location of artisanal and small-scale gold mining (ASGM) in this study are in Anggai village and Air Mangga village in Obi sub-district, South Halmahera district, North Maluku Province. Amalgamation has been the preferred method for treating the gold ores in both Anggai and Air Mangga Villages. The methodology provides a suggested approach for collecting and analyzing data and guidance for analyzing policy, regulatory, and institutional aspects and health aspects in the ASGM sector, mainly covering the Socio Economy ASGM research methodology. An assessment of the practicality of a proposed plan or project is also called Feasibility Study. The objective of this research was to describe the socio-economic impact and feasibility of gold processing of ASGM in Obi Island, South Halmahera district, North Maluku Province.